Targeting 4-1BB for tumor immunotherapy from bench to bedside - Wang, Ya-Tao; Ji, Wei-Dong; Jiao, Hong-Mei; Lu, Ang; Chen, Kun-Feng; Liu, Qi-Bing (Frontiers in Immunology, 2022)
Immune dysfunction has been proposed as a factor that may contribute to disease progression. Emerging evidence suggests that immunotherapy aims to abolish cancer progression by modulating the balance of the tumor microenvironment. 4-1BB (also known as CD137 and TNFRS9), a member of tumor necrosis factor receptor superfamily, has been validated as an extremely attractive and promising target for immunotherapy due to the upregulated expression in the tumor environment and its involvement in tumor progression. More importantly, 4-1BB-based immunotherapy approaches have manifested powerful antitumor effects in clinical trials targeting 4-1BB alone or in combination with other immune checkpoints. In this review, we will summarize the structure and expression of 4-1BB and its ligand, discuss the role of 4-1BB in the microenvironment and tumor progression, and update the development of drugs targeting 4-1BB. The purpose of the review is to furnish a comprehensive overview of the potential of 4-1BB as an immunotherapeutic target and to discuss recent advances and prospects for 4-1BB in cancer therapy.